Outpatient administration of CAR T-cell therapy: a focused review with recommendations for implementation in community based centers - Perez, Ariel; Al Sagheer, Tiba; Nahas, George R.; Linhares, Yuliya P. L. (Frontiers in Immunology, 2024)
Chimeric Antigen Receptor T-cell (CAR-T) therapy has transformed the treatment landscape for hematological malignancies, showing high efficacy in patients with relapsed or refractory (R/R) disease and otherwise poor prognosis in the pre-CAR-T era. These therapies have been usually administered in the inpatient setting due to the risk of cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity syndrome (ICANS). However, there is a growing interest in the transition to outpatient administration due to multiple reasons. We review available evidence regarding safety and feasibility of outpatient administration of CD19 targeted and BCMA targeted CAR T-cell therapy with an emphasis on the implementation of outpatient CAR-T programs in community-based centers.